Purification treatment method of industrial acidic wastewater
By using alkaline agent pretreatment and purification adsorbents with optimized components in acidic wastewater treatment, the problems of high cost and low efficiency in the treatment of acidic mine wastewater in the existing technology are solved, and efficient heavy metal ion adsorption and water purification effects are achieved. Comply with green environmental protection requirements.
Patent Information
- Application Number
- CN202411860745.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing mine acidic wastewater treatment methods have high cost and low efficiency, and are prone to secondary pollution.
Use an alkaline -based pharmaceutical pre -treatment of acidic wastewater, and by optimizing and purifying the composition ratio of absorbers, preparing recycled use, green and environmentally friendly -free purification -free purification adsorbent, including molration and coal ash, composite bumps, modified chitosan, modified chitosan, and modified chitosan, and modified chitosan, and modified chitosan, and modified chitosan, and modified chitosan, and modified chitosan, and modified chitosan, and modified chitosan, and modified chitosan, and modified shells, modified chitosan, and modified chitosa, and modified shells. Polinal soil, sodium silicate and removing water are performed and maintained, and finally put them in pre -treatment waste liquid for intermittent stirring and filtering.
It effectively improves the heavy metal ion pollution of acidic wastewater, achieves water purification effects, improves the structural stability and heavy metal ion adsorption capacity of the purification adsorbent, meets the requirements of green production, and achieves the purpose of solid waste resource utilization and wastewater treatment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, in particular to a method for purifying industrial acidic wastewater. Background Art
[0002] Mining activities, exposure of open-pit mines, etc. will produce acidic wastewater. Since acidic wastewater has a low pH value and contains a large amount of heavy metal ions such as copper, nickel, mercury, cadmium, lead, and chromium, direct discharge will cause water acidification and destroy the water's self-purification function. At the same time, it will poison the soil and vegetation and affect the sustainable development of the production area.
[0003] The existing methods for treating acid mine wastewater are mainly divided into neutralization method, sulfide precipitation method and microbial method. However, most of the existing methods have high treatment costs, low efficiency, and are prone to secondary pollution. Summary of the invention
[0004] The purpose of the present invention is to provide a method for purifying industrial acidic wastewater to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for purifying industrial acidic wastewater comprises the following steps: S1: adding alkaline reagent into industrial acidic wastewater, stirring, standing and filtering to obtain pretreated waste liquid; S2: mixing fly ash, composite attapulgite, modified chitosan, bentonite, sodium silicate and deionized water, granulating and curing to obtain a purification adsorbent; S3: adding the purification adsorbent into the pre-treated waste liquid, stirring and filtering intermittently to obtain the treated waste liquid.
[0006] Furthermore, the alkaline agent is one or a combination of calcium oxide, calcium hydroxide, sodium hydroxide, sodium carbonate, and sodium bicarbonate.
[0007] Furthermore, the pH of the industrial acidic wastewater is 1-5, and the pH of the pretreated wastewater is 6-8.
[0008] Furthermore, the mass volume ratio of the purified adsorbent to the pretreated waste liquid is 8g:10L.
[0009] Furthermore, the working conditions of intermittent stirring are: stirring for 10-20 minutes after feeding, and stirring for 10 minutes every 1 hour until adsorption is completed.
[0010] Furthermore, the raw material composition of the purification adsorbent is: 27-37 parts of fly ash, 13-25 parts of composite attapulgite, 3-10 parts of modified chitosan, 2-5 parts of bentonite, 1-3 parts of sodium silicate, and 3-8 parts of deionized water.
[0011] By optimizing the composition ratio of the purification adsorbent, a recyclable, green and environmentally friendly purification adsorbent with strong heavy metal adsorption capacity is prepared. When purifying industrial acidic wastewater, it can effectively improve the heavy metal ion pollution of acidic wastewater and achieve water purification effect.
[0012] Solid waste powder fly ash, bio-material chitosan and renewable attapulgite are selected as raw materials, mixed with bentonite, sodium silicate and deionized water to form granules to prepare spherical purification adsorbents, which meets the current green production requirements. By controlling the ingredient ratio, the structural stability of the purification adsorbent is greatly improved, thereby increasing its adsorption capacity for heavy metal ions and pollutants, thereby achieving the purpose of solid waste resource utilization.
[0013] Further, the preparation of the composite attapulgite comprises the following steps: 1) Under a nitrogen atmosphere, sodium sulfide solution and attapulgite are mixed, stirred for 1-2 hours, a mixed solution of ascorbic acid and deionized water is added, and a ferrous sulfate solution is added, ultrasonically stirred for 15-20 minutes, filtered, and freeze-dried to obtain pretreated attapulgite; 2) Pretreated attapulgite, deionized water, carbodiimide hydrochloride, N-hydroxysuccinimide, and a carboxyl-containing amine polymer are mixed, and the temperature is raised to 70-80° C. and kept for 2-3 hours to obtain composite attapulgite.
[0014] In order to improve the adsorption and purification capacity of attapulgite and improve its uniformity of dispersion in the purification adsorbent, the method of co-precipitation of ascorbic acid and nano-FeS on attapulgite was adopted to obtain pretreated attapulgite, and then the polyhydroxy structure of ascorbic acid was used to graft amine polymers containing carboxyl groups, wherein the amine polymers containing carboxyl groups were acid- and alkali-resistant Bronsted acid proton buffered polyamines, which can greatly improve the stability of the purification adsorbent and the adsorption capacity for heavy metal ions such as cadmium, lead, and chromium.
[0015] Further, the preparation of modified chitosan comprises the following steps: (1) Mix chitosan, methanol and glutaraldehyde solution, keep warm in a water bath at 53-57°C for 5-6 hours, wash and dry to obtain cross-linked chitosan; mix cross-linked chitosan, NaOH solution and epichlorohydrin, shake in a water bath at 38-42°C for 3-4 hours, wash to neutrality to obtain epoxy chitosan; (3) Mixing the carboxyl-containing amine polymer and NaOH solution, adding epoxy chitosan, shaking in a water bath at 68-72°C for 5-6 hours, washing, and drying to obtain modified chitosan.
[0016] Chitosan is selected as a binder. In order to improve the water solubility and stability of chitosan, the chitosan is modified. First, the chitosan is cross-linked with glutaraldehyde, and then reacted with epichlorohydrin under alkaline conditions to introduce epoxy groups. The epoxy groups are reacted with amine polymers containing carboxyl groups to prepare modified chitosan, which has a composite effect on fly ash and composite attapulgite and bentonite, improves the bonding strength between the purification adsorbent raw materials, reduces the amount of sludge, and synergistically improves the adsorption effect of the adsorbent on pollutants.
[0017] Furthermore, the mass ratio of the carboxyl-containing amine polymer to epoxy chitosan is 0.8:1.
[0018] Further, the preparation of the amine polymer containing carboxyl groups comprises the following steps: In a nitrogen atmosphere, 2-(trifluoromethyl)acrylic acid, methanol, trimethylolpropane trimethacrylate, 4-vinylaniline and azobisisobutyronitrile are mixed, kept at 68-72°C for 22-24 hours, filtered, washed and ground to obtain an amine polymer containing a carboxyl group.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for purifying industrial acidic wastewater. By optimizing the component ratio of the purification adsorbent used, a recyclable, green and environmentally friendly, combustion-free purification adsorbent with high heavy metal adsorption capacity is prepared. When used for purifying industrial acidic wastewater, the pollution of the acidic wastewater can be effectively improved.
[0020] In the present invention, solid waste powder fly ash, bio-material chitosan, and renewable attapulgite are selected as raw materials, which are mixed with bentonite, sodium silicate, and deionized water to form granules to prepare spherical purification adsorbents, which meets the requirements of green production. By controlling the ingredient ratio, the structural stability of the adsorbent is improved, thereby improving its adsorption capacity for heavy metal ions and pollutants, thereby achieving the purpose of solid waste resource utilization and wastewater treatment.
[0021] In order to improve the adsorption and purification capacity of attapulgite and its uniformity of dispersion in the adsorbent, the method of co-precipitation of ascorbic acid and nano-FeS on attapulgite was adopted to obtain pretreated attapulgite, and then the polyhydroxy structure of ascorbic acid was used to graft amine polymers containing carboxyl groups. The amine polymers containing carboxyl groups were polymerized with 2-(trifluoromethyl) acrylic acid as the functional monomer for storing protons, 4-vinylaniline as the amino monomer and trimethylolpropane trimethacrylate as the cross-linking agent. The prepared amine polymers containing carboxyl groups were acid- and alkali-resistant Bronsted acid proton buffered polyamines, which greatly improved the stability of the purification adsorbent and the adsorption capacity for heavy metal ions such as cadmium, lead and chromium.
[0022] In the present invention, chitosan is selected as a binder. In order to improve the water solubility and stability of chitosan, the chitosan is modified. First, the chitosan is cross-linked and modified with glutaraldehyde, and then reacted with epichlorohydrin under alkaline conditions to introduce epoxy groups. The epoxy groups are reacted with amine polymers containing carboxyl groups to prepare modified chitosan, which has a composite effect on fly ash and composite attapulgite and bentonite, improves the strength of the combination between the purification adsorbent raw materials, reduces the amount of sediment, and synergistically improves the adsorption effect of the adsorbent, thereby improving the adsorption effect of the pollutants. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0025] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0026] Embodiment 1: A method for purifying industrial acidic wastewater, comprising the following steps: S1: adding alkaline reagent into industrial acidic wastewater, stirring, standing and filtering to obtain pretreated waste liquid; The alkaline agent is calcium oxide; the pH of the industrial acidic wastewater is 1, and the pH of the pretreated waste liquid is 6; S2: mixing fly ash, composite attapulgite, modified chitosan, bentonite, sodium silicate and deionized water, granulating and curing to obtain a purification adsorbent; In parts by weight, the raw material composition of the purification adsorbent is: 27 parts of fly ash, 13 parts of composite attapulgite, 3 parts of modified chitosan, 2 parts of bentonite, 1 part of sodium silicate, and 3 parts of deionized water; The working conditions for curing are: stand for 6 hours, heat up to 65℃ and keep for 2 hours, heat up to 95℃ and keep for 2 hours, heat up to 115℃ and keep for 2 hours, cool down to 25℃; The preparation of the composite attapulgite comprises the following steps: 1) Under a nitrogen atmosphere, 100 mL of 1 mol / L sodium sulfide solution and 2 g of attapulgite were mixed, stirred for 1 h, 0.25 g of ascorbic acid and 250 mL of deionized water were added, 100 mL of 1 mol / L ferrous sulfate solution was added, ultrasonic stirring was performed for 15 min, filtration was performed, and freeze-drying was performed to obtain pretreated attapulgite; 2) 8.4 g of pretreated attapulgite, 100 mL of deionized water, 1.8 g of carbodiimide hydrochloride, 0.9 g of N-hydroxysuccinimide, and 3.7 g of an amine polymer containing a carboxyl group were mixed, and the temperature was raised to 70° C. and kept for 3 h to obtain composite attapulgite; The preparation of the modified chitosan comprises the following steps: (1) Mix 1 g of chitosan, 30 mL of methanol, and 6 mL of 10% glutaraldehyde solution, keep it in a 53°C water bath for 6 h, wash and dry it to obtain cross-linked chitosan; mix 1 g of cross-linked chitosan, 30 mL of 1 mol / L NaOH solution, and 4 mL of epichlorohydrin, shake it in a 38°C water bath for 4 h, wash it to neutrality, and obtain epoxy chitosan; (3) 0.8 g of an amine polymer containing a carboxyl group and 30 mL of 1 mol / L NaOH solution were mixed, 1 g of epoxy chitosan was added, and the mixture was shaken in a water bath at 68 °C for 6 h, washed, and dried to obtain modified chitosan; The preparation of the carboxyl-containing amine polymer comprises the following steps: Under nitrogen atmosphere, 0.5mmol 2-(trifluoromethyl)acrylic acid, 5mL methanol, 0.5mmol trimethylolpropane trimethacrylate, 2mmol 4-vinylaniline, and 50mg azobisisobutyronitrile were mixed, kept at 68℃ for 24h, filtered, washed, and ground to obtain an amine polymer containing a carboxyl group; S3: adding the purification adsorbent to the pre-treated waste liquid, stirring and filtering intermittently to obtain the treated waste liquid; The mass volume ratio of the purified adsorbent to the pretreated waste liquid is 8 g:10 L; The working conditions of intermittent stirring are: stirring for 10 minutes after adding the materials, and stirring for 10 minutes every 1 hour until the adsorption is completed.
[0027] Embodiment 2: A method for purifying industrial acidic wastewater, comprising the following steps: S1: adding alkaline reagent into industrial acidic wastewater, stirring, standing and filtering to obtain pretreated waste liquid; The alkaline agent is calcium oxide; the pH of the industrial acidic wastewater is 3, and the pH of the pretreated waste liquid is 7; S2: mixing fly ash, composite attapulgite, modified chitosan, bentonite, sodium silicate and deionized water, granulating and curing to obtain a purification adsorbent; In parts by weight, the raw material composition of the purification adsorbent is: 32 parts of fly ash, 19 parts of composite attapulgite, 7 parts of modified chitosan, 3 parts of bentonite, 2 parts of sodium silicate, and 5 parts of deionized water; The working conditions for curing are: stand for 6 hours, heat up to 65℃ and keep for 2 hours, heat up to 95℃ and keep for 2 hours, heat up to 115℃ and keep for 2 hours, cool down to 25℃; The preparation of the composite attapulgite comprises the following steps: 1) Under a nitrogen atmosphere, 100 mL of 1 mol / L sodium sulfide solution and 2 g of attapulgite were mixed, stirred for 1.5 h, a mixture of 0.25 g of ascorbic acid and 250 mL of deionized water was added, and 100 mL of 1 mol / L ferrous sulfate solution was added, ultrasonically stirred for 18 min, filtered, and freeze-dried to obtain pretreated attapulgite; 2) 8.4 g of pretreated attapulgite, 100 mL of deionized water, 1.8 g of carbodiimide hydrochloride, 0.9 g of N-hydroxysuccinimide, and 3.7 g of an amine polymer containing a carboxyl group were mixed, and the temperature was raised to 75° C. and kept for 2.5 h to obtain composite attapulgite; The preparation of the modified chitosan comprises the following steps: (1) Mix 1 g of chitosan, 30 mL of methanol, and 6 mL of 10% glutaraldehyde solution, keep it in a 55°C water bath for 5.5 h, wash and dry it to obtain cross-linked chitosan; mix 1 g of cross-linked chitosan, 30 mL of 1 mol / L NaOH solution, and 4 mL of epichlorohydrin, shake it in a 40°C water bath for 3.5 h, wash it to neutrality, and obtain epoxy chitosan; (3) 0.8 g of an amine polymer containing a carboxyl group and 30 mL of 1 mol / L NaOH solution were mixed, 1 g of epoxy chitosan was added, and the mixture was shaken in a water bath at 70 °C for 5.5 h, washed, and dried to obtain modified chitosan; The preparation of the carboxyl-containing amine polymer comprises the following steps: Under nitrogen atmosphere, 0.5mmol 2-(trifluoromethyl)acrylic acid, 5mL methanol, 0.5mmol trimethylolpropane trimethacrylate, 2mmol 4-vinylaniline, and 50mg azobisisobutyronitrile were mixed, kept at 70℃ for 23h, filtered, washed, and ground to obtain an amine polymer containing a carboxyl group; S3: adding the purification adsorbent to the pre-treated waste liquid, stirring and filtering intermittently to obtain the treated waste liquid; The mass volume ratio of the purified adsorbent to the pretreated waste liquid is 8 g:10 L; The working conditions of intermittent stirring are: stirring for 15 minutes after adding the materials, and stirring for 10 minutes every 1 hour until the adsorption is completed.
[0028] Embodiment 3: A method for purifying industrial acidic wastewater, comprising the following steps: S1: adding alkaline reagent into industrial acidic wastewater, stirring, standing and filtering to obtain pretreated waste liquid; The alkaline agent is calcium oxide; the pH of the industrial acidic wastewater is 5, and the pH of the pretreated waste liquid is 8; S2: mixing fly ash, composite attapulgite, modified chitosan, bentonite, sodium silicate and deionized water, granulating and curing to obtain a purification adsorbent; In parts by weight, the raw material composition of the purification adsorbent is: 37 parts of fly ash, 25 parts of composite attapulgite, 10 parts of modified chitosan, 5 parts of bentonite, 3 parts of sodium silicate, and 8 parts of deionized water; The working conditions for curing are: stand for 6 hours, heat up to 65℃ and keep for 2 hours, heat up to 95℃ and keep for 2 hours, heat up to 115℃ and keep for 2 hours, cool down to 25℃; The preparation of the composite attapulgite comprises the following steps: 1) Under a nitrogen atmosphere, 100 mL of 1 mol / L sodium sulfide solution and 2 g of attapulgite were mixed, stirred for 2 h, 0.25 g of ascorbic acid and 250 mL of deionized water were added, 100 mL of 1 mol / L ferrous sulfate solution was added, ultrasonic stirring was performed for 20 min, filtration was performed, and freeze-drying was performed to obtain pretreated attapulgite; 2) 8.4 g of pretreated attapulgite, 100 mL of deionized water, 1.8 g of carbodiimide hydrochloride, 0.9 g of N-hydroxysuccinimide, and 3.7 g of an amine polymer containing a carboxyl group were mixed, and the temperature was raised to 80° C. and kept for 2 h to obtain composite attapulgite; The preparation of the modified chitosan comprises the following steps: (1) Mix 1 g of chitosan, 30 mL of methanol, and 6 mL of 10% glutaraldehyde solution, keep it in a 57°C water bath for 5 h, wash and dry it to obtain cross-linked chitosan; mix 1 g of cross-linked chitosan, 30 mL of 1 mol / L NaOH solution, and 4 mL of epichlorohydrin, shake it in a 42°C water bath for 3 h, wash it to neutrality, and obtain epoxy chitosan; (3) 0.8 g of an amine polymer containing a carboxyl group and 30 mL of 1 mol / L NaOH solution were mixed, 1 g of epoxy chitosan was added, and the mixture was shaken in a water bath at 72 °C for 5 h, washed, and dried to obtain modified chitosan; The preparation of the carboxyl-containing amine polymer comprises the following steps: Under nitrogen atmosphere, 0.5mmol 2-(trifluoromethyl)acrylic acid, 5mL methanol, 0.5mmol trimethylolpropane trimethacrylate, 2mmol 4-vinylaniline, and 50mg azobisisobutyronitrile were mixed, kept at 72℃ for 22h, filtered, washed, and ground to obtain an amine polymer containing a carboxyl group; S3: adding the purification adsorbent to the pre-treated waste liquid, stirring and filtering intermittently to obtain the treated waste liquid; The mass volume ratio of the purified adsorbent to the pretreated waste liquid is 8 g:10 L; The working conditions of intermittent stirring are: stirring for 20 minutes after adding the materials, and stirring for 10 minutes every 1 hour until the adsorption is completed.
[0029] Comparative Example 1: Taking Example 3 as the control group, attapulgite was used to replace the composite attapulgite, and the other processes were normal.
[0030] Comparative Example 2: Taking Example 3 as the control group, chitosan was used to replace the modified chitosan, and the other processes were normal.
[0031] Comparative Example 3: Example 3 was used as a control group, in which no amine polymer containing a carboxyl group was prepared, and other processes were normal.
[0032] Sources of raw materials used (for demonstration purposes only): Fly ash (3µm): Main components: by mass fraction, silicon dioxide 51.5%, aluminum oxide 26.8%, calcium oxide 5.5%, iron oxide 4.5%, magnesium oxide 0.1%; bentonite (5µm, 99%): Hubei Kewode Chemical Co., Ltd.; attapulgite M62688: Shanghai Myrel Biochemical Technology Co., Ltd.; ascorbic acid A103533, ferrous sulfate F116338, carbodiimide hydrochloride E106172, N-hydroxysuccinimide N164062, chitosan C105802, glutaraldehyde G105905, epichlorohydrin E108182, 2-(trifluoromethyl)acrylic acid T109983, trimethylolpropane trimethacrylate T131641, 4-vinylaniline A151485, azobisisobutyronitrile A434183: Aladdin reagent; calcium oxide, methanol, sodium silicate, sodium sulfide, NaOH, analytical grade: Sinopharm reagent.
[0033] Performance Testing: The purification agent was used to cycle the wastewater for 5 times, and then the adsorption capacity of cadmium ions and chromium ions was tested: Configuration 100mL100mg / LCr 6+ The test liquid is used as wastewater to test the adsorption capacity of chromium ions; 100mL100mg / LCd 2+The test liquid was used as wastewater to test the adsorption capacity of cadmium ions; the removal rate D was (A0-Ai) / A0×100%, A0-initial concentration, Ai-concentration after adsorption; the results are shown in Table 1; Table 1
[0034] The present invention provides a method for purifying industrial acidic wastewater. By optimizing the component ratio of the purification adsorbent used, a recyclable, green and environmentally friendly, combustion-free purification adsorbent with high heavy metal adsorption capacity is prepared. When used for purifying industrial acidic wastewater, the pollution of the acidic wastewater can be effectively improved.
[0035] By comparing Example 3 with Comparative Examples 1 and 3, it can be seen that in order to improve the adsorption and purification capacity of attapulgite and the uniformity of its dispersion in the adsorbent, a method of co-precipitating ascorbic acid and nano-FeS on attapulgite is used to obtain pretreated attapulgite, and then the polyhydroxy structure of ascorbic acid is used to graft an amine polymer containing a carboxyl group, wherein the amine polymer containing a carboxyl group uses 2-(trifluoromethyl)acrylic acid as a functional monomer for storing protons, and is polymerized with an amino monomer 4-vinylaniline and a cross-linking agent trimethylolpropane trimethacrylate. The prepared amine polymer containing a carboxyl group is an acid- and alkali-resistant Bronsted acid proton buffered polyamine, which greatly improves the stability of the purification adsorbent and the adsorption capacity for heavy metal ions such as mercury, lead, and chromium.
[0036] By comparing Example 3 with Comparative Examples 2 and 3, it can be seen that chitosan is selected as a binder in the present invention. In order to improve the water solubility and stability of chitosan, the chitosan is modified. The chitosan is first cross-linked with glutaraldehyde and then reacted with epichlorohydrin under alkaline conditions to introduce epoxy groups. The epoxy groups are reacted with amine polymers containing carboxyl groups to prepare modified chitosan, which has a composite effect on fly ash and composite attapulgite and bentonite, improves the strength of the bonding between the purification adsorbent raw materials, reduces the amount of sludge, and synergistically improves the adsorption effect on pollutants.
[0037] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for purifying industrial acidic wastewater, characterized in that: The following steps are involved: S1: adding alkaline reagent into industrial acidic wastewater, stirring, standing and filtering to obtain pretreated waste liquid; S2: mixing fly ash, composite attapulgite, modified chitosan, bentonite, sodium silicate and deionized water, granulating and curing to obtain a purification adsorbent; S3: Adding the purification adsorbent into the pre-treated waste liquid, stirring and filtering intermittently to obtain the treated waste liquid.
2. The method for purifying industrial acidic wastewater according to claim 1, characterized in that: The alkaline agent is one or a combination of calcium oxide, calcium hydroxide, sodium hydroxide, sodium carbonate and sodium bicarbonate.
3. The method for purifying industrial acidic wastewater according to claim 1, characterized in that: In step S1, the pH of the industrial acidic wastewater is 1-5, and the pH of the pretreated waste liquid is 6-8.
4. The method for purifying industrial acidic wastewater according to claim 1, characterized in that: The mass volume ratio of the purified adsorbent to the pretreated waste liquid is 8g:10L.
5. The method for purifying industrial acidic wastewater according to claim 1, characterized in that: The working conditions of intermittent stirring are: stirring for 10-20 minutes after adding the materials, and stirring for 10 minutes every 1 hour until the adsorption is completed.
6. The method for purifying industrial acidic wastewater according to claim 1, characterized in that: The raw material composition of the purification adsorbent is as follows, in parts by weight: 27-37 parts of fly ash, 13-25 parts of composite attapulgite, 3-10 parts of modified chitosan, 2-5 parts of bentonite, 1-3 parts of sodium silicate, and 3-8 parts of deionized water.
7. The method for purifying industrial acidic wastewater according to claim 1, characterized in that: The preparation of the composite attapulgite comprises the following steps: 1) Under a nitrogen atmosphere, sodium sulfide solution and attapulgite are mixed, stirred for 1-2 hours, a mixed solution of ascorbic acid and deionized water is added, and a ferrous sulfate solution is added, ultrasonically stirred for 15-20 minutes, filtered, and freeze-dried to obtain pretreated attapulgite; 2) Pretreated attapulgite, deionized water, carbodiimide hydrochloride, N-hydroxysuccinimide, and a carboxyl-containing amine polymer are mixed, and the temperature is raised to 70-80° C. and kept for 2-3 hours to obtain composite attapulgite.
8. The method for purifying industrial acidic wastewater according to claim 1, characterized in that: The preparation of the modified chitosan comprises the following steps: (1) Mix chitosan, methanol and glutaraldehyde solution, keep warm in a water bath at 53-57°C for 5-6 hours, wash and dry to obtain cross-linked chitosan; mix cross-linked chitosan, NaOH solution and epichlorohydrin, shake in a water bath at 38-42°C for 3-4 hours, wash to neutrality to obtain epoxy chitosan; (2) Mixing the carboxyl-containing amine polymer and NaOH solution, adding epoxy chitosan, shaking in a water bath at 68-72°C for 5-6 hours, washing, and drying to obtain modified chitosan.
9. The method for purifying industrial acidic wastewater according to claim 8, characterized in that: In the preparation of modified chitosan, the mass ratio of the carboxyl-containing amine polymer to epoxy chitosan is 0.8:
1.
10. A method for purifying industrial acidic wastewater according to claim 7 or 8, characterized in that: The preparation of the carboxyl-containing amine polymer comprises the following steps: In a nitrogen atmosphere, 2-(trifluoromethyl)acrylic acid, methanol, trimethylolpropane trimethacrylate, 4-vinylaniline and azobisisobutyronitrile are mixed, kept at 68-72°C for 22-24 hours, filtered, washed and ground to obtain an amine polymer containing a carboxyl group.
Citation Information
Patent Citations
Polyethylene imine -attapulgite adsorbent preparation and hexavalent chromium adsorption method
CN103831089A
Chemical-biological composite functional material for improving black stinky bottom mud and preparation process of composite functional material
CN108751634A
Composite sewage treatment agent based on inorganic non-metallic mineral material and application
CN111704194A
Adsorbent for industrial sewage treatment and preparation method thereof
CN112892504A
Carboxyl-rich attapulgite composite material as well as preparation method and application thereof
CN115350682A